Importance of Detoxification Processes in Ozone Risk Assessment: Need to Integrate the Cellular Compartmentation of Antioxidants? - Dusart, Nicolas; Gandin, Anthony; Vaultier, Marie-Noëlle; Joffe, Ricardo; Cabané, Mireille; Dizengremel, Pierre; Jolivet, Yves (Frontiers in Forests and Global Change, 2019)
The correct integration of the detoxification processes in a risk assessment model for ozone damage on plants remains challenging. In particular, the intracellular compartmentation of antioxidant metabolites could play a role, since each compartment presents its own sensitivity to ROS and metabolite set. For each cell compartment, the main metabolites were presented as well as the putative transporters implied. Clearly, under O3 exposure integrative data which would allow to improve predictive models for ozone risk assessment are missing.